2017
DOI: 10.1016/j.cej.2016.12.058
|View full text |Cite
|
Sign up to set email alerts
|

Exploring beyond palladium: Catalytic reduction of aqueous oxyanion pollutants with alternative platinum group metals and new mechanistic implications

Abstract: For over two decades, Pd has been the primary hydrogenation metal studied for reductive catalytic water treatment applications. Herein, we report that alternative platinum group metals (Rh, Ru, Pt and Ir) can exhibit substantially higher activity, wider substrate selectivity and variable pH dependence in comparison to Pd. Cross comparison of multiple metals and oxyanion substrates provides new mechanistic insights into the heterogeneous reactions. Activity differences and pH effects mainly originate from the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 56 publications
1
54
1
Order By: Relevance
“…The higher reactivity of monometallic Ru/C than Pd/C is especially noteworthy because the Pd/C reactivity observed in Fig. 1 is actually much greater than that reported in earlier studies that found either no reaction with nitrate or a very low extent of reaction [30,31,56,[74][75][76]. Trawczyński et al [71] calculated TOF 0 of nitrate reduction on an in-house prepared Pd/C catalyst to be ~0.03 min -1 , which is one order-of-magnitude lower than the TOF 0 calculated from data for Pd/C in Fig.…”
Section: Methodscontrasting
confidence: 49%
See 1 more Smart Citation
“…The higher reactivity of monometallic Ru/C than Pd/C is especially noteworthy because the Pd/C reactivity observed in Fig. 1 is actually much greater than that reported in earlier studies that found either no reaction with nitrate or a very low extent of reaction [30,31,56,[74][75][76]. Trawczyński et al [71] calculated TOF 0 of nitrate reduction on an in-house prepared Pd/C catalyst to be ~0.03 min -1 , which is one order-of-magnitude lower than the TOF 0 calculated from data for Pd/C in Fig.…”
Section: Methodscontrasting
confidence: 49%
“…After recently screening a range of metal catalysts as alternatives to Pd for reduction of oxyanion pollutants [56], this contribution focuses on a renewed evaluation of the kinetics and mechanisms of nitrate and nitrite reduction by supported Ru catalysts. Reaction kinetics, product distribution analysis, and catalyst characterization studies are combined with Density Functional Theory (DFT) calculations to improve our understanding of interaction between nitrate (and nitrite) and Ru metal surfaces and elucidate the origin of endproduct selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…These large nanoparticles favor H 2 activation making easy the H 2 dissociative adsorption due to enhanced solubility of H 2 and formation of β‐PdH species [40] . This has been observed in many hydrogenation reaction when using Pd catalysts [23,41–43] and could explain the highest TOF obtained with the catalyst with the largest Pd mean crystal size. This explanation is appropriate for alumina catalysts where bromate adsorption is not hindered for the existence of a negative surface charge on the catalyst surface, but would not be valid for other type of supports.…”
Section: Resultsmentioning
confidence: 88%
“…Different noble metals supported on diverse materials have been studied as catalysts for this reaction [22–23] concluding that this technique could be adequate for the removal of bromate in polluted water at room temperature and atmospheric pressure. The use of Pd catalysts supported on carbon nanofibers with a continuous reactor has been reported showing good results even using natural and industrial water polluted by bromate [24] .…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, Pt-catalysts were more active than the Pd catalysts when mesoporous SBA-15 was used as support, suggesting that other properties related to the support affect the catalytic behavior [62]. Other authors compared the catalytic removal of bromates using commercial catalysts based on activated carbon or alumina with different metals such as Pd, Pt, Ru, Rh, and Ir [63]. Results revealed different catalytic performances depending on the selected metal, metal content and, medium pH.…”
Section: Catalysts For the Bromate Hydrogenation 21 Influence Of Thmentioning
confidence: 99%